English Speaking Problems and Solutions between Employees and Customers in Workplaces - Papawadee Dayama; Nuttaput Mokmas; Pawee Onouhn; Apinya Manochphinyo (Jurnal Bahasa Inggris Terapan, 2021)
Language is a very important tool for human communication. To be successful in speaking, people may use both verbal and non-verbal communication. Using effective communication may not be easy for many people. This study examined 40 Thai employees and 17 foreign customers from three hotels and three tour agencies in Trang, Thailand. The data for this study were collected through a questionnaire from 40 Thai employees. 17 foreign customers answered two open-ended questions, and then the interview was asked. The participants answered about problems and solutions in speaking English. The finding of this study showed that most employees and foreign customers had more verbal communication than non-verbal communication. However, they used several solutions to solve those problems based on their perspectives and experiences.